ASSOCIATION OF rs4537545 (C>T) ALLELE POLYMORPHISM IN THE IL6R GENE WITH THE DEVELOPMENT OF RHEUMATOID ARTHRITIS - L. V. Topchieva; I. E. Malysheva; O. V. Balan; I. M. Marusenko; O. Yu. Barysheva (Научно-практическая ревматология)
Objective: to analyze the association of the polymorphic marker rs4537545 (C>T) in the IL6R gene with the development of rheumatoid arthritis (RA) in the population of the Republic of Karelia. Subjects and methods. The investigation included 190 samples of DNA extracted from the whole blood of healthy individuals and 158 samples from patients with RA. Genotyping was performed using a polymerase chain reaction (PCR)-restriction fragment length polymorphism analysis. The expression level of IL6 and IL6R genes in peripheral blood leukocytes (PBLs) from healthy individuals was assessed by real-time PCR. The plasma content of interleukin-6 (IL-6) in healthy donors was measured by enzyme-linked immunosorbent assay (ELISA). Results and discussion. An association of the polymorphic marker rs4537545 (C>T) in the IL6R gene with the development of rheumatoid arthritis was found in the population of the Republic of Karelia. The risk of RA in the persons carrying the T-allele of rs4537545 in the genotypes was 2.1 times higher than that in the C-allele carriers (odds ratio (OR), 2.103; 95% confidence interval, 1.032-4.287). The genotypes were ascertained to have an effect on the level of IL6R gene in PBL and on the plasma content of IL-6 in the healthy donors. Conclusion. The polymorphic marker rs4537545 (C>T) in the IL6R gene is involved in the genetic predisposition of humans to RA development through modulation of the level of transcriptional activity of the IL6R gene and the content of IL-6.